Organizational and National Aspects of the Union for the Liberation of Ukraine Activities in the Camps for Captured Ukrainians of the Tsarist Army in Germany between 1914 and 1918 - Ihor Sribnyak; Natalia Yakovenko; Viktor Matviyenko (Przegląd Nauk Historycznych)
The article aims to analyse selected aspects of organisational and national activities of the Union for the Liberation of Ukraine (ULU) in the Prisoner-of-War Camps of Captured Ukrainians from the Tsarist Army during the First World War. To accomplish this task, the ULU involved a number of Galician and Bukovyna intellectuals (educators and writers), whose actions initially provided for a selection of captured Ukrainians in multinational camps and who were transferred to the future Ukrainian camps in Rastatt, Wetzlar and Salzwedel between May and November 1915. In each of these camps, the ULU educational departments were established and their members were engaged in uniting prisoners in Ukrainian communities and acted as mediators between camp commandants and camp residents in addition to conducting various educational presentations and courses. They were in direct contact with the Heads of the Ukrainian communities of the camps, seeing them daily for joint meetings. The free course of Ukrainian life in the camps caused the development of a national worldview among the vast majority of prisoners of these camps. Soon after, the elected representative bodies of Ukrainian prisoners took over not only the functions of educational departments, but also the general leadership of Ukrainian communities. Due to this, it became possible to raise among the prisoners nationally conscious citizens for the future Ukrainian state, ready to come forward with weapons in their hands to defend Ukraine against the Bolshevik attacks.